Possibly propylthiouracil-induced antineutrophilic cytoplasmic antibody-associated vasculitis manifested as blood coagulation disorders: A case report. Issue 41 (October 2016) - Yi, Xiao-Yan; Wang, Yao; Li, Qi-Fu; Li, Rong; Yang, Shu-Min; Zhou, Guo-Qing; Wang, Zhi-Hong
Abstract: Background: Propylthiouracil is the most common drug used to treat hyperthyroidism. However, this drug could cause a severe disease, antineutrophilic cytoplasmic antibody-associated vasculitis (AAV), which was usually misdiagnosed. Methods: We reported a 60-year-old woman of propylthiouracil-induced AAV manifested as blood coagulation disorders. The patient was admitted because of hyperthyroidism and leukopenia. At the time of hospitalization, she suffered from dry cough, erythema and knee joints ache, and gradually became febrile. And then BP decreased and PLT was reduced with coagulation disorders. ANCA: c-ANCA positive (1:100), p-ANCA positive (1:320), MPO-IgG positive, PR3-IgG positive, GBM-IgG negative. Erythrocyte sedimentation rate and C-reactive protein increased markedly. Chest high-resolution computed tomography (HRCT) showed that scattered spots, patch and ground-glass opacity. Results: Finally, we made a terminal diagnosis of PTU-induced AAV possibly. After drug withdrawal and use of steroid, the patient recovered well and then accepted RAI therapy. As the patient was given imipenem-cilastatin before the reduction of PLT and coagulation disorders, we considered that the hematologic disorders might be caused by antibiotics or a clinical presentation of the vasculitis itself. Conclusion: Drug-induced vasculitis is relatively good prognosis, but early diagnosis and timely withdrawal of associated drugs are the key to the treatment.